Fidelity or love the one you're with? Biotic complexity and tradeoffs can drive strategy and specificity in beetle‐fungus by‐product mutualisms - Diana L. Six; Peter H. W. Biedermann (Ecology and Evolution)
Abstract By‐product mutualisms are ubiquitous yet seldom considered in models of mutualism. Most models represent conditional mutualisms that shift between mutualism and antagonism in response to shifts in costs and benefits resulting from changes in environmental quality. However, in by‐product mutualisms, benefits arise as a part of normal life processes that may be costly to produce but incur little‐to‐no additional costs in response to the interaction. Without costs associated with the interaction, they do not have antagonistic alternate states. Here, we present a conceptual model that differs from traditional conditional models in three ways: (1) partners exchange by‐product benefits, (2) interactions do not have alternate antagonistic states, and (3) tradeoffs are allowed among factors that influence environmental quality (rather than all factors that contribute to environmental quality being combined into a single gradient ranging from high to low). We applied this model to bark and ambrosia beetles (Curculionidae: Scolytinae), a diverse group that associates with fungi and that has repeatedly developed two distinct pathways to by‐product mutualism. We used independent axes for each major factor influencing environmental quality in these systems, including those that exhibit tradeoffs (tree defense and nutritional quality). For these symbioses, tradeoffs in these two factors are key to which mutualism pathway is taken.